Bioresorbable scaffolds and drug-eluting balloons for the management of spontaneous coronary artery dissections - Panoulas, Vasileios F.; Ielasi, Alfonso (Journal of Thoracic Disease, 2016)
Spontaneous coronary artery dissection (SCAD) is well recognised cause of acute coronary syndromes (ACS), typically affecting female and younger individuals with no underlying atherosclerotic disease (1). SCAD is a relatively rare presentation of ACS however its reported prevalence varies from as low as 0.2% in angiographic studies (2) to as high as 4% of ACS cases in studies using optimal coherence tomography (OCT) (3).